Penerapan Metode Adaptie Neuro Fuzzy Inference dalam Memprediksi Penjualan Buku - Zulfia Darma; Agus Perdana Windarto; Dedi Suhendro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The increase in sales of items or product componies continues to increase based on the needs of the community. With the increase in sales will greatly affect the income of a company. So a mature sales strategy is needed. The number of visitors has a great influence on sales transactions. The more visitors, the more likely the transaction can be predicted. The number of visitors every day is different and has an unequal percentage in making sales transactions. One way to increase sales revenue is to predict sales based on the average number of stock so that sales strategy planning can be right on target. Related to this, the author conducts research to predict the number of book sales based on the pattern that occurs from the number of book stock at PT. Tiga Serangkai Pustaka Mandiri Pematangsiantar. By applying the Adaptive Neuro Fuzzy Inference System (ANFIS) method in predicting book sales in 2018-2020. The amount of data used is 36 data, divided into training data (23 data) and testing (13 data) using 2 input variables namely orders and stock, 1 input variable is sales. In testing with matlab software, the training process uses mf trimf with 9 rules which produces the smallest error value of 1.045 at epoch 36, with an accuracy rate of 57%